Maharashtra State BoardSSC (English Medium) 9th Standard
Advertisement Remove all ads

If P ( Y ) = Y 2 − 3 √ 2 Y + 1 Then Find P ( 3 √ 2 ) . - Algebra

Sum

If p(y) = `y^2 - 3sqrt2 + 1` then find  `p (3sqrt 2)`.

Advertisement Remove all ads

Solution

` p(y) = y^2 - 3sqrt2 + 1`

`therefore p(3 sqrt 2) = (3 sqrt 2)^2 - 3sqrt 2 xx 3 sqrt 2 + 1 = 18 - 18 + 1 = 1`

Concept: Value of a Polynomial
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Balbharati Mathematics 1 Algebra 9th Standard Maharashtra State Board
Chapter 3 Polynomials
Practice Set 3.4 | Q 2 | Page 48
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×